(untitled) - Fabozzi, Frank J. (Hoboken, NJ, 2002)
The Global Money Markets is the authoritative source on short-term investing and borrowing-from instruments in the U.S. and U.K., to asset-liability management. It also clearly demonstrates the various conventions used for money market calculations and discusses other short-term structured financial products such as asset-backed securities and mortgage-backed securities.
Keywords: Money market,International finance,Thị trường tiền tệ,Tài chính quốc tế